A death in the dark - Alexander, Ellie (Alexander, Ellie. Novel detectives, 2026)
"When beloved local teacher and track coach Josh Bynum stumbles into the Secret Bookcase distressed and with no memory of the previous night, Annie's and Fletcher's instincts tell them something doesn't add up. As the duo delve deeper into the tight-knit world of high school athletics, they uncover a web of secrets. Between ambitious parents, suspicious fundraising activities, and a star athlete with a lot to lose, everyone has something to hide. Annie and Fletcher will need all their investigative skills and the support of their Redwood Grove friends if they're to solve this mystery. Has Josh been set up? And what if there's a clever killer somewhere in their beloved hometown, who might decide to target them next?"--Amazon.